Improved version of authentication scheme for GNSS signal using Raspberry Pi - Kho, Jane Shwu Tyng (Nanyang Technological University, 2023)
The Global Navigation Satellite System (GNSS) is a constellation of satellites that provide positioning, navigation, and timing (PNT) services to a wide range of applications, including transportation, communication, and defense. However, the GNSS signals are vulnerable to various attacks, such as spoofing, man-in-the-middle attack and jamming, which compromise the integrity and authenticity of the signals. This may result in detrimental damages and can be a catastrophe event for nation if a national attack occurs. To enhance the security of GNSS signals, typically Global Positioning System (GPS) signal, various authentication and encryption techniques have been proposed, including Chameleon Hashing. In this final year project, Chameleon Hashing, a certificateless cryptography and authentication scheme had implemented on Raspberry Pi to authenticate and encrypt GNSS signal, which is the GPS signal in this case. The Internet of things (IoT) device was able to identify between spoofed and genuine GPS signals. Typical implementation of Chameleon Hashing technique still exist the risk of man-in-the-middle (MITM) attacks. Therefore, in this final year project, the author addressed this issue by providing a time gap during the transmission of Hash-based Message Authentication Code (HMAC) and hash key. This is achieved by reducing the receiving subframes from actual 5 to 3 subframes, which provides 12 seconds extra for gapping the reference HMAC and hash key transmission.